Multi-attribute monitoring applications in biopharmaceutical analysis - Anurag S. Rathore; Deepika Sarin; Sanghati Bhattacharya; Sunil Kumar (Journal of Chromatography Open, 2024)
Since the introduction of Quality by Design for production of biopharmaceuticals, the global biopharma industry has been advancing towards developing highly efficient and sensitive platforms for monitoring product quality attributes. Incorporating mass-spectrometry-based multi-attribute monitoring (MAM) as a novel tool for identifying and characterizing post-translational modifications in biotherapeutics has gained increasing traction. The ability of MAM to monitor multiple critical quality attributes coupled with new peak detection functions in a single workflow is highly desirable to the biopharmaceutical industry. This review examines and discusses the evolution and adaptation of MAM for routine product quality assessment. MAM applications in biotherapeutic characterization, comparability, and chemometrics have also been discussed, along with the gaps and future perspectives of the MAM implementation in biopharmaceutical drug development. Primary focus has been kept on major developments in last 6 years (2018–2024).